PENGGUNAAN PYTHON PYSIMPLEGUI UNTUK MENINGKATKAN KETERAMPILAN SKILL SISWA TIK SMP - Sudirman T.P Lumbangaol; Sitorus, Peniel Sam Putra; Eduward Situmorang; Rektor Sianturi; Lampola Sitorus (Yayasan Nusantara Hasana Berdikari, 2025)
Schools in Indonesia are an important environment for developing character, communication and the growth of students' minds in pursuing science and technology. Science and technology continue to develop, and human resources must be improved to keep up with these developments. The Indonesian state has a target to become a Golden Indonesia by 2045, with a focus on developing science and technology in balance with existing human resources. In the era of technology 5.0, schools in Indonesia are faced with the challenge of integrating increasingly advanced technology into education, so curriculum changes are being made to maintain the relevance of education with technological developments. Basic education in Indonesia has included programming language subjects, which are important in the development of technology and applications. At this time, the Python programming language is increasingly popular, because it is easy to understand by novice users and has many uses in various industrial fields. Python can be used to create desktop, mobile, game and other based programs. Its easy-to-understand nature makes it popular among technology developers. Python also has many benefits, such as flexibility in using libraries to create applications and analysis. This programming language allows the implementation of the concepts of inheritance and polymorphism, so it is widely used in various operating systems. Secondary schools in Indonesia also focus on developing students' individual skills through an independent learning curriculum, which includes ICT subjects and programming languages. The Python programming language and the use of pysimplegui are encouraged to improve students' skills in technology. Through this research, it is hoped that it can increase understanding and use of the Python programming language pysimplegui in junior high schools (SMP) to help students develop skills and knowledge in technology.